PENERAPAN MODEL KOOPERATIF DALAM PEMBELAJARAN VPN SERVER MASA PANDEMI COVID-19 - Fajar Bakhrun Najkhi (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
This research aims to determine the implementation of online learning in SMK on VPN Server material combining cooperative learning models and simulation methods through real experience-based learning. The research subjects were students of class XII TKJ. The research method uses a descriptive qualitative approach that records activities along with student learning achievements in online learning. The application of the learning model combines a group of teachers, a group of teachers to a heterogeneous student study group. Miles & Huberman model as a data analysis technique. The results of the study showed that 80% of cognitive learning achievement achieved a value of 95-100 and 1 student who obtained 80-82, 66.66% psychomotor students scored 79-100 and 33% between 75-78. The impact of the study was: facilitating teachers in online learning, providing students with real experiences with simulation and cooperative methods, and parents obtaining information on the progress of student learning outcomes in the publication of their work on the teacher's web blog.